Morphological features and anatomical structure of the leaves of Dagestan endemic species of Allium - Z. R. Ramazanova; M. D. Dibirov; Z. I. Soltanmuradova; Z. M. Asadulaev (Юг России: экология, развитие)
Aim. To conduct a comparative analysis and assessment of the taxon specificity of the morphological and anatomical features of the leaves of endemic species of the genus Allium in Dagestan.   Material and Methods. The research materials were samples of endemic species of the genus Allium from the natural populations of mountainous Dagestan: A. daghestanicum; A. gunibicum; A. charadzeae; A. mirzojevii and A. samurense. For the analysis of morphometric features, 10 generative individuals were collected in the full flowering phase. Processing of the collected material was carried out at the Laboratory of Introduction and Genetic Resources of the Mountain Botanical Garden, Dagestan Federal Research Centre, Russian Academy of Sciences. Fixation of the material and preparation of temporary micropreparations were carried out according to the generally accepted methods of anatomical studies. Anatomical studies were carried out on leaves of medium formation from the middle part of the leaf. Morphometric parameters of tissues and cells were measured using a Levenhuk D870T optical microscope with an eyepiece micrometer. Micropreparations were photographed using a Lomo‐AT 054 optical microscope and a DCM 510 SCOP video eyepiece.   Results. A grouping of species according to leaf size was carried out: large‐leaved (A. daghestanicum, A. gunibicum, A charadze section Dagestanica. Tscholok. Friesen) and small‐leaved (A. mirzojevii, A. samurense section Oreiprason F. Herm.), according to the shape of the leaf cross section: grooved with smooth edges (A. daghestanicum), grooved with ribbed edges (A. gunibicum and A charadze) and rounded ribbed (A. mirzojevii and A. samurense), according to the number and size of vascular bundles. Descriptions of the anatomical structure of the leaves and an assessment of the species specificity of the studied traits of five species of Allium were carried out.   Conclusions. It was determined that some features of the morphology and anatomy of the leaves of five endemic species of the genus Allium are species‐specific or due to environmental conditions of growth in the arid conditions of Inner Mountain Dagestan.